Pengembangan Paltform Layanan Konsultasi Kecantikan Online Untuk Meningkatkan Industri Ekonomi Digital Kreatif di Indonesia - Rosita, Putri Aulia; Nuryananda, Praja Firdaus (UNIB Press, 2024)
The platform business model is a simple yet powerful concept that radically alters business, the financial system, and society in general. The platform revolution threatens almost all industries that rely heavily on information. This concept evolved into a view of the interdependence of innovation and technological advancement, which influences both macro and microeconomics. whomever decides how far digital technology can travel. The MBKM initiative exists to strengthen the creative digital economy in Indonesia, and one of the outcomes of this study was the creation of an online beauty consultation service platform.